2013
DOI: 10.1111/1469-0691.12174
|View full text |Cite
|
Sign up to set email alerts
|

Lack of nasal carriage of novel corona virus (HCoV-EMC) in French Hajj pilgrims returning from the Hajj 2012, despite a high rate of respiratory symptoms

Abstract: A cohort of 154 French Hajj pilgrims participating in the 2012 Hajj were systematically sampled with nasal swabs prior to returning to France, and screened for the novel HCoV-EMC coronavirus by two real-time RT-PCR assays. Despite a high rate of respiratory symptoms (83.4%), including 41.0% influenza-like illness, no case of HCoV-EMC infection was detected. Despite the fact that zoonotic transmission was suspected in the first few cases, a recent family cluster in the Kingdom of Saudi Arabia suggests that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 9 publications
9
76
1
Order By: Relevance
“…However, a strength of our study is that we tested almost 1000 children hospitalized with ARI symptoms for MERS-CoV. Of note, another study described lack of detecting MERS-CoV from nasal swabs from a group of French Hajj pilgrims after returning to France, despite a high rate of respiratory symptoms [15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, a strength of our study is that we tested almost 1000 children hospitalized with ARI symptoms for MERS-CoV. Of note, another study described lack of detecting MERS-CoV from nasal swabs from a group of French Hajj pilgrims after returning to France, despite a high rate of respiratory symptoms [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the Saudi Arabian MOH confirmed that admissions of respiratory cases to Hajj hospitals had been within the expected range for the 2012 Hajj. Respiratory tract swabs of hospitalized patients-190 from Medina hospitals and another 86 from Mecca hospitals -tested negative for nCoV molecular targets, as did swabs from 154 pilgrims tested on return home to France [10]. More recently the Saudi Arabian MOH, through its leadership of the newly established collaborating Centre for Mass Gatherings Medicine, will conduct cross-sectional and longitudinal studies on nCoV and other respiratory tract infections for surveillance, prevention and control.…”
Section: Hajj Studies and Collaborationsmentioning
confidence: 99%
“…Surveillance efforts, since the discovery of the virus and retrospective testing of stored respiratory specimens suggest this is not the case (Gautret et al, 2013). In August, 2013, the possible source of MERS-COV virus was traced to an Egyptian tomb bat found in a building, in close proximity to an index patient home.…”
Section: Introductionmentioning
confidence: 99%